Rancang Bangun Sistem Informasi Produksi Neonbox (SIPRON) Pada Arrasyi Neonbox Bandung - Faza, Auliya Urrahim; Akbar, Muhammad Faris; Darmawan, Eka Putera; Khairunnisa, Ifa; Effendi, Diana (Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the production sector often face challenges such as manual data recording, lack of system integration, and difficulties in managing raw materials and production processes. Arrasyi Neonbox Bandung, as a production-based MSME, experiences similar issues that impact production delays and operational inefficiency. This study aims to design and develop a web-based Neonbox Production Information System (SIPRON) that integrates order management, raw materials, production processes, and reporting. The research employs a quantitative method with a prototyping approach, enabling iterative interaction between developers and users. System evaluation was conducted using a Likert-scale questionnaire distributed to users. The results indicate that the developed system improves efficiency and integration of production processes. The user satisfaction index reached 84%, categorized as very satisfied. Therefore, SIPRON is considered effective in supporting MSME operations and addressing the limitations of previously fragmented systems.